Cooperative resource allocation algorithms in cellular orthogonal frequency-division multiple access systems for target signal-to-interference plus noise ratio provision - Hosseini Andargoli, Seyed Mehdi; Mohamed-pour, Kamal (IET communications, 2014)
This study addresses subcarrier allocation and power distribution in a sectorised two-cell downlink orthogonal frequency-division multiple access system impaired by multicell interference. The objective is to maximise the sum spectral efficiency in a way that the signal-to-interference plus noise ratio (SINR) of the transmitted data substream on each subcarrier meets a target SINR. In cellular systems because of intercell interference, it may not be possible to guarantee the target SINR in all cells simultaneously; therefore the authors have suggested a cooperative resource allocation algorithm which tries to provide the target SINR per subcarrier in all cells through cooperation in the interference control. For a considered subcarrier, if achieving the target SINR is impossible by the interference reduction, one base station avoids transmission on the considered subcarrier so that another base station can meet the target SINR. For complexity reduction, a simplified resource allocation algorithm is then provided based on the separation of subcarrier allocation and power control. Simulation results show that the proposed algorithms not only guarantee the target SINR but achieve more sum spectral efficiency than benchmark algorithms in many practical situations.